Philosophy of ‘Egek’ Culture From The Moi Tribe of Papua in Exposing The Concept of Environmental Accounting (A Phenomenological Study) - Patma, Kurniawan; Kambuaya, Maylen K.P. (AIBPM Publisher, 2024)
Recent sustainability concerns have extended their influence into the realm of accounting. Previously, annual financial reporting held primary importance for companies, but now, in response to these concerns, a settlement report has been introduced, reflecting the emergence of environmental accounting. Researchers employed the Egek Culture from Moi Tribe phenomenological philosophy study method to uncover how green accounting is rooted in cultural values. Data analysis involved interviews with seasoned experts in environmental accounting to gather insights from informants. The selection of divided methods reveals the values of indigenous Papua culture in the concept of environmental accounting. The study found that green accounting has not received serious optimal development in Indonesia. To apply green accounting effectively, there is a need to align the proposed concept with existing international guidelines. The Egek philosophy offers insights into resolving key issues in green accounting since it strives to fulfill the social and environmental responsibilities of an entity to the utmost extent possible. Applying green accounting via the phenomenological approach of Egek philosophy enhances understanding comprehensively.